Manajemen Keuangan Pribadi: Literasi Ekonomi, Literasi Keuangan, dan Kecerdasan Spiritual - Lilik Sri Hariani; Endah Andayani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
Personal financial management is the activity of planning, organizing, directing, and supervising financial activities such as the procurement and use of funds owned for the survival of the family. Many factors influence personal financial management. This study aims to analyze economic literacy, financial literacy, and spiritual intelligence on personal financial management. This study used a quantitative descriptive approach, with a sample of 73 housewives in Malang City who were taken randomly. Data collection using questionnaires and data analysis using Multiple Linear Regression analysis. The results showed that economic literacy, financial literacy, and spiritual intelligence simultaneously affect personal financial management, financial literacy and spiritual intelligence partially affect personal financial management, while economic literacy partially has no effect on personal financial management. As a housewife who usually acts as a manager in the family, at least you must understand two main concepts in financial management, namely the concept of cost and benefit and the concept of cash flow. For further researchers, it can expand the sample and add other variables so that it can better describe how financial management is for the people of Malang.